Effects of Allium siculum in ethylene glycol induced kidney stone in male albino rats - Mahmud, Sarbast Ahmad; Aveen R. Khdhr; Abdulsamih M. Taha; Payam M. Abdulla; Kurdo B. Chato (Kuwait Journal of Science, 2021)
The current study attempts to find the curative effects of Allium siculum on ethylene glycol induced kidney stone in male albino rats. Twenty two male albino rats were divided into four experimental groups. Group A represented the control. Group B, C and D animals received 1% ethylene glycol in water for 14 days, then from day 15 to day 28 the treatment of ethylene glycol stopped and group C and D animals from day 15 to day 28 received Allium siculum (5% crude extract in water and standard diet) and cystone (2.5 tablets in water and standard diet) respectively. Serum uric acid, creatinine, urea, lipid measurements and glucose were evaluated besides the kidneys weight and body weight gain. Allium siculum and cystone treatments indicated significant reduction in serum uric acid, creatinine, urea, glucose, very low density lipoprotein and triglyceride compared to ethylene glycol treated rats. Furthermore, the kidneys weight and body weight gains significantly increased in group B as compared with A, C and D. Whereas, the values of cholesterol, non-high density lipoprotein cholesterol, low density lipoprotein, high density lipoprotein and low density lipoprotein/ high density lipoprotein ratio didn’t show significant differences in any experimental groups. In conclusion: Allium siculum has a strong curative effects which resembled the cystone drug.